2021
DOI: 10.1063/5.0055535
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional single framework multicomponent lattice Boltzmann equation method for vesicle hydrodynamics

Abstract: 2021). Three-dimensional single framework multi-component lattice Boltzmann equation method for vesicle hydrodynamics. Physics of Fluids, 33 (7), 077110.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…While such experimental data are available, albeit scarce, for rigid particles in suspension, e.g., based on nuclear magnetic resonance measurements of particle profiles, the authors are not aware of any such data for soft vesicles, in particular RBCs. Here again, we hope eventually to use our recent meso-scale models (MCLBM) which account for the cellular-scale interactions in full detail [11] to refine and parameterise a constitutive equation for concentrated suspensions of deformable vesicles and hence to inform the present continuum model parameters. The results presented here provide us with the reassurance that, the final discussions below notwithstanding, a suitably sensitive, macro-scale model exists for this undertaking.…”
Section: Limitations Of the Model And Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…While such experimental data are available, albeit scarce, for rigid particles in suspension, e.g., based on nuclear magnetic resonance measurements of particle profiles, the authors are not aware of any such data for soft vesicles, in particular RBCs. Here again, we hope eventually to use our recent meso-scale models (MCLBM) which account for the cellular-scale interactions in full detail [11] to refine and parameterise a constitutive equation for concentrated suspensions of deformable vesicles and hence to inform the present continuum model parameters. The results presented here provide us with the reassurance that, the final discussions below notwithstanding, a suitably sensitive, macro-scale model exists for this undertaking.…”
Section: Limitations Of the Model And Future Workmentioning
confidence: 99%
“…Meso-scale modelling, e.g., Particle Dynamics Methods [4], or the multi-component Lattice Boltzmann Method [5] has a widely acknowledged facility for Lagrangian particulate flows [6][7][8][9][10] and has been employed to describe these interactions and the dynamics of the collisions in detail. Very recently, we have developed a single framework, three-dimensional methodology for capturing detailed, particle-scale interactions between neutrally buoyant suspended vesicles (i.e., erythrocytes), using our novel chromodynamics multi-component Lattice Boltzmann method variant [11]. We have previously shown that this same essential model is able to capture detailed hydrodynamic interactions, lubrication effects and ballistic collisions between transported particles, in two dimensional simulations containing O(1000) liquid drops at high volume faction [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these established, multi-framework approaches, we recently presented a complementary, single-framework, chromodynamic multi-component lattice Boltzmann method (cMCLBM), adapted to vesicle hydrodynamics (specifically RBCs), the scope of which we extend here. We have addressed verification of physical content, based upon steady state and dynamical data on single RBC deformation [14]. The model was shown to be a promising tool, practically and theoretically, its foundations (kinematics and dy-namics) being carefully constructed from prior art [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…-To outline an extension to cMCLBM [14], which facilitates the simulation of multiple, immiscible fluid objects of variable character, as mutually immiscible fluid components -To verify this single-framework, enhanced cMCLBM for multiple fluid objects, to verify that suspensions of liquid drops, erythrocytes, and other vesicles then fall within the scope of the method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation